1998
DOI: 10.1038/sj.onc.1201855
|View full text |Cite
|
Sign up to set email alerts
|

Point mutation and homozygous deletion of PTEN/MMAC1 in primary bladder cancers

Abstract: A new tumor suppressor gene PTEN/MMAC1 was recently isolated at chromosome 10q23 and found to be inactivated by point mutation or homozygous deletion in glioma, prostate and breast cancer. PTEN/MMAC1 was also identi®ed as the gene predisposing to Cowden disease, an autosomal dominant cancer predisposition syndrome associated with an increased risk of breast, skin and thyroid tumors and occasional cases of other cancers including bladder and renal cell carcinoma. We screened 345 urinary tract cancers by microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(186 citation statements)
references
References 12 publications
10
173
1
2
Order By: Relevance
“…While Steck et al (11) reported mutations in one of four primary renal carcinomas, later, larger studies have found no, or very few, PTEN/MMAC1 mutations in RCC (13)(14)(15)(16)(17). Furthermore, observations in other human tumor types have also shown few PTEN/MMAC1 mutations despite high LOH rates at the gene locus (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Steck et al (11) reported mutations in one of four primary renal carcinomas, later, larger studies have found no, or very few, PTEN/MMAC1 mutations in RCC (13)(14)(15)(16)(17). Furthermore, observations in other human tumor types have also shown few PTEN/MMAC1 mutations despite high LOH rates at the gene locus (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Initial screens of 9 RCCs seemed to support this hypothesis, showing loss of heterozygosity (LOH) in 40% of tumors and mutations in 15% of tumors (11,12). However, two subsequent larger studies failed to detect any mutations (13,14). Recently, Alimov et al (15) reported a 34% LOH rate at 10q23-25 but found only three mutations when they screened the subset of tumors that displayed LOH for mutations; Kondo et al (16) detected only five mutations, some of which were heterozygote, in a series of 68 sporadic renal cell carcinomas; and Sukosd et al (17) found high rates of 10q23.3 LOH in chRCC, but only in 2 of 50 cRCC, and detected no PTEN/MMAC1 mutations in the tumors with LOH.…”
mentioning
confidence: 98%
“…In particular, the mutation of PTEN appears with a frequency of up to 50% in endometrial cancer (Tashiro et al, 1997) compared with other cancers, including glioblastoma (28%), prostate cancer (30%), and melanoma (15%) (Dahia, 2000). Abnormalities in the expression of the PTEN gene have been shown in esophageal cancer, melanoma, and prostate cancer (Cairns et al, 1997;Whang et al, 1998). Gene silencing by promoter methylation of PTEN has been reported in endometrial and prostate cancer (Salvesen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Among these mutations are structural rearrangements within the PTEN gene (intragenic inversions, insertions, deletions and duplications known as gross PTEN mutations) that occur in BRCA1-associated basal-like breast cancer (Saal et al, 2008). PTEN mutation frequencies affecting both alleles in various cancers are: endometrial (B50%), glioblastoma (B30%), prostate (B10%), and breast (B5%) (Cairns et al, , 1998Steck et al, 1997;Tashiro et al, 1997;Wang et al, 1997;Chiariello et al, 1998;Duerr et al, 1998;Lin et al, 1998;Shao et al, 1998;Ali et al, 1999;Zhou et al, 2002;Saal et al, 2005). The monoalleleic loss of PTEN is regularly observed in a considerable fraction of malignancies at the following frequencies: glioma (B75%), breast (B40-50%), colon (B20%), lung (B37%), prostate (B42%) (Teng et al, 1997;Bose et al, 1998;Feilotter et al, 1998;Lin et al, 1998;Rubin et al, 2000).…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 99%
“…Sequencing of the PTEN gene in tumors found it to be one of the most commonly mutated tumor suppressors in human malignancies Rasheed et al, 1997;Tashiro et al, 1997;Wang et al, 1997Wang et al, , 1998Cairns et al, 1998;Duerr et al, 1998;Shao et al, 1998). The hereditary loss of PTEN leads to numerous autosomal dominant disorders: Cowden syndrome, Bannayan-Riley-Ruvalcaba syndrome, Lhermitte-Duclos disease, Proteus syndrome and Proteuslike syndrome, which are characterized by the presence of developmental defects, benign hamartomas and an increased risk of cancer Marsh et al, 1997;Zhou et al, 2000Zhou et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%